Production of Citric Acid from Oil Palm Empty Fruit Bunches by Solid State Bioconversion using Local Aspergillus niger - Alam, Md. Zahangir; Abdul Karim, Mohamed Ismail; Jamal, Parveen; Al-Mamun, Abdullah; Bari, Md. Niamul (2010)
Malaysia is the largest oil palm (Elaeis guianeensis) plantation country in the world and annually produce 17.08 million tons empty fruit bunches (EFB) as solid waste (Chew and Bhatia, 2008). The oil palm biomass including EFB is burnt as fuel in the boiler to produce steam for electricity generation as well as processing of palm oil fruits (Nasrin et al., 2008). At present, little amount of the biomass is used in the plantation as much to provide organic nutrients to the oil palm trees (Suhaimi and Ong, 2001). However, this method is not feasible due to the exorbitant collection and transportation cost as well as difficulty in spreading uniformly over the land. The other way of disposal of EFB is burning illegally, which contributes to the air pollution (Suhaimi and Ong, 2001). Burning is now prohibited by regulations to prevent air pollution. Oil palm biomass is also being used for composite boards, pulp, paper, cushions, landscaping, etc. Nevertheless, the volume of oil palm biomass produced annually is much larger than the amount used in these processes. Therefore, the rest of the biomass poses serious disposal problems in the environment. The disposal of EFB as solid waste by open dumping in lowlands poses great environmental problems, such as soil pollution as well as water pollution, while disposal by proper sanitary landfill is considered a huge economic concern (Weng, 2005). Most of the industrial solid wastes in Malaysia are disposed off by landfill (Begum et al, 2007); whereas, dumping can itself be a problem because of scarcity of enough lowlands to be used as landfill site.